HISTORICAL-THEORETICAL ASPECTS OF STATE POWER SEPARATION THEORY FORMATION AND DEVELOPMENT - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose of the study is to analyze the issues of theory to determine the principle of separation of powers. Achieving this goal is ensured through the search for scientific-theoretical constructions on specific historical-legal material. Research methods: of the work is a comprehensive approach to the analysis of the theory of separation of powers, its development. It is based on the dialectical method of research, analytical methods, comparison, and historicism, which provide identification of the inner essence of phenomena through the characteristics of the dynamics of their development and external manifestations. Results: are represented by the demonstration of one of the problems of the theory of the organization of state power. In our opinion, the materials of the paper can be used to prepare new courses on Theory of State and Law, Constitutional Law, Political Science Theory, which are taught in higher education institutions of Ukraine. Discussion: of the obtained results is that the paper attempts to show and analyze the problem of the theory of the organization of state power. The conclusions suggested by the author are important for the further development of the theory of separation of powers and in-depth scientific research of legal problems of practical implementation of this theory in state-building practice. The research materials can be used in the direct practical activities of representatives of various branches of government, statesmen and political leaders. In addition to the scientific significance, as well as the possibilities of application in the educational process of this paper, it should be indicated its relevance to the legislative process. The practical significance of the article is that it is a contribution to the formation of the scientific-theoretical basis of legislative activity.